Perceptions of access and benefits from community-based aquaculture through Photovoice: A case study within a locally managed marine area in Madagascar. (1st May 2022) - Funk, Lara; Wilson, A. Meriwether W.; Gough, Charlotte; Brayne, Kitty; Djerryh, Noelinaud Robert
Abstract: Small-scale fishers face a range of local and global environmental pressures including declining fish stocks and climate change. In coastal southwest Madagascar, community-based aquaculture (CBA) projects have been established within a locally managed marine area (LMMA) to provide alternative income streams for small-scale fishing communities and support community efforts in reducing local fishing pressures. This study focused on understanding community perceptions of both access to, and benefits from, two CBA projects within the Velondriake LMMA involving seaweed and sea cucumber aquaculture. Participants included seaweed farmers, sea cucumber farmers, and non-farmers, and research considered the impacts of the projects at the individual and community level. Participatory field research was conducted in Tampolove, Madagascar during 2018 using an adapted Photovoice method with participant-based photos and in-depth interviews. The integration of CBA projects into the LMMA resulted in a new governance model, with the aquaculture sites requiring 'private access' within a historically 'open-access' setting. Results showed that community members accepted this access change for the community's coastal area, with aquaculture benefits including more predictable income generation and benefit-sharing across the community, appearing to outweigh the loss of access to part of their traditional fishing grounds. However, further research is required to better understand how women and other marginalised community members are affected. Due to the benefits cited by community members, the CBA-LMMA model may have applicability to other coastal community settings in the Western Indian Ocean (WIO) where there is both a need and opportunity for positive alignment of community-based alternative livelihoods and marine conservation.